The Rhetorical Function of Portraits from Benin (Nigeria) - Sweet Ufumwen Ebeigbe , (Wacana Seni Journal of Arts Discourse, 2013)
A scrutiny of African portraiture art reveals that it is atypical in style, diverse in function and inherent in complex connotations. Consequently, this genre amongst the creative outputs of Africans is generally not properly comprehended outside their culture of origin, hence little has been written about them. It is therefore unsurprising that some arguments in literature actually assert that African art is devoid of portraits. On the contrary and as countless examples show, Africans, for example, the people of Benin (Nigeria) produce veritable portraits. The most intriguing aspects of these artforms, from an art historical perspective, are their unusual formal configuration, profound aesthetic and iconographic significance, multifarious style and diverse functions. These singular characteristics differentiate them from non-African portraits and are their own unique property. They are also the features that make them interesting and edifying. Thus the aim of this article is principally to present a contextual analysis of Benin portraits in an attempt to explicate the aesthetic and iconographic concerns hat make them significant. This appraisal is aimed also at promoting further knowledge and appreciation of these artforms outside their culture of origin.